Scribal intrusion in the texts of "Gamelyn" - Vázquez, Nila (Adam Mickiewicz University, 2010)
One of most important steps in the process of editing a manuscript is the identification and correction of the mistakes made by the scribe or scribes involved in its copying process in order to obtain the best text. In some cases, the changes introduced by the scribe, or by the editor who was supervising his work, can easily be noticed because we find out “physical” elements throughout the folio, such as dots under a word as a sign of expunction or carets indicating that a missing word is being added. However, there are many instances of scribal intrusion where only a detailed analysis of the text itself, or even the comparison of different manuscripts, can lead us to the identification of a modified reading. For instance, orthographical changes due to the dialectal provenance of the copyist, or altered lines with a regular aspect. The purpose of this article is to analyse the scribal amendments that appear in some of the earliest copies of The tale of Gamelyn: Corpus Christi College Oxford MS 198 (Cp), Christ Church Oxford MS 152 (Ch), Fitzwilliam Museum McClean 181 (Fi), British Library MS Harley 7334 (Ha4), Bodleian Library MS Hatton Donat. 1 (Ht), British Library MS Lansdowne 851 (La), Lichfield Cathedral MS 29 (Lc), Cambridge University Library Mm.2.5 (Mm), Petworth House MS 7 (Pw) and British Library MS Royal 18 C.II (Ry2).